2004
DOI: 10.1021/jf0306035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dissolved Organic Carbon of Soil Amendments with Aging:  Effect on Pesticide Adsorption Behavior

Abstract: The effect of aging in the soil of three organic amendments (OAs), one liquid (LF) and two solid ones (SF and AL), has been investigated and related to changes in soil adsorption of metalaxyl and tricyclazole. LF and AL have very high dissolved organic carbon (DOC) contents with low humification index values, whereas SF has a low DOC content but the highest amounts of highly humified material. All OAs increased the adsorption of tricyclazole, whereas adsorption of metalaxyl decreased in soils amended with LF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 44 publications
3
34
0
1
Order By: Relevance
“…These amounts are 4.6 times higher than that obtained when only micronutrients were applied in the soil (0.96%, Fig. 2), and this increases because of the formation of DOM-diuron complexes as observed previously (Thevenot et al, 2008;Cox et al, 2004;El Imache et al, 2012). Although SS and USR supply different DOM concentrations to soil (0.28 and 0.04 mg DOM/g of soil, respectively), a similar diuron extraction was obtained, indicating that the quality of DOM supplied plays also an important role in diuron availability.…”
Section: Effect Of Composts On Soil Diuron Mineralisationsupporting
confidence: 59%
“…These amounts are 4.6 times higher than that obtained when only micronutrients were applied in the soil (0.96%, Fig. 2), and this increases because of the formation of DOM-diuron complexes as observed previously (Thevenot et al, 2008;Cox et al, 2004;El Imache et al, 2012). Although SS and USR supply different DOM concentrations to soil (0.28 and 0.04 mg DOM/g of soil, respectively), a similar diuron extraction was obtained, indicating that the quality of DOM supplied plays also an important role in diuron availability.…”
Section: Effect Of Composts On Soil Diuron Mineralisationsupporting
confidence: 59%
“…The isotherms exhibit increasing non-linearity with AC, B4, and the mixture amendment, corresponding to the increasing deviation from 1 of ŋ f values in the Freundlich model (Table 6). This suggests a significant solute adsorption on a small amount of a high-surface area material in soil and to specific interactions of tricyclazole with highly reactive sites provided for the organic matter from the amendment, supporting previous results obtained with other amendments and other sorbents [61,68]. The curvilinear isotherm indicates that the number of available sites for the adsorption turned into a limiting factor at the higher concentrations of tricyclazole.…”
Section: Adsorption and Desorption Experimentssupporting
confidence: 85%
“…They observed a lower sorption of pesticides with macadamia nut shell biochar compared to wood chip pellet biochar. This result was attributed to the higher content of dissolved organic carbon in this biochar, which can compete with pesticides for mineral soil surfaces and thus decrease pesticide sorption (Cox et al, 2004). Martin et al (2012) observed differences in the sorption capacity between biochars freshly spread or in place for 3 years.…”
Section: Organic Pollutantsmentioning
confidence: 94%